2006
DOI: 10.1096/fj.05-5510fje
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine‐induced activation of dopamine receptors modulates FGF‐2 expression in astrocytic cultures and promotes survival of dopaminergic neurons

Abstract: Apomorphine (APO), a potent D1/D2 dopamine receptor agonist, is currently used as an antiparkinsonian drug. We have shown previously that APO stimulates synthesis and release of multiple trophic factors, such as brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF), in both mesencephalic and striatal neurons, thereby effectively preventing dopaminergic neuron loss in vitro. The present study was designed to investigate the effects of APO on fibroblast growth factor-2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…The conditioned medium (CM) was prepared as described previously (Li et al, 2006). Postnatal striatal astrocytes were allowed to grow to 90% confluence and maintained with FBS-free DMEM/Ham's F12 medium containing SKF83959 or APO for 24 h after pretreatment with or without 50 M SCH23390.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conditioned medium (CM) was prepared as described previously (Li et al, 2006). Postnatal striatal astrocytes were allowed to grow to 90% confluence and maintained with FBS-free DMEM/Ham's F12 medium containing SKF83959 or APO for 24 h after pretreatment with or without 50 M SCH23390.…”
Section: Animalsmentioning
confidence: 99%
“…Western blotting was performed as described previously (Li et al, 2006). The following primary antibodies were used: (a) rabbit anti-FGF-2 pAb (1:300; Santa Cruz Biotechnology); (b) rabbit anti-BDNF pAb (1:200; Santa Cruz Biotechnology); (c) rabbit anti-GDNF pAb (1:500; Santa Cruz Biotechnology); (d) rabbit anti-neurotrophin-3 (NT-3; 1:200; Santa Cruz Biotechnology); (e) mouse anti-␣-tubulin monoclonal antibody (mAb; 1:4000; Sigma); (f) mouse anti-␤-actin mAb (1:5000; Sigma); (g) rabbit anti-phosphoCaMKII␣ pAb (1:500; Cell Signaling Technology).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the increase in GDNF and BDNF levels, treatment with apomorphine also increases FGF-2 expression in striatal astrocytes, both at the mRNA and protein level, an effect correlated with the activation of D1 and D2 receptors (Li et al, 2006a). FGF-2 exerts a potent neuroprotective action on nigral dopaminergic neurons in the MPTP mouse model of PD Unsicker, 1990, 1993;Chadi et al, 1993).…”
Section: Dopamine Agonistsmentioning
confidence: 99%
“…FGF distinguishes itself from other neurotrophic factors due to its critical role in supporting developing and adult DA systems [22,23]. FGF-2 promotes the growth and survival of cultured DA neurons [24][25][26], protects against neurotoxin-induced cell death [27][28][29][30][31][32] and cografting of DA neurons with FGF-2 increases neuronal survival [17,33,34]. It was reported that FGF signaling increases DA levels in calbindin-negative SN neurons, those at greatest risk in PD patients [35].…”
Section: Introductionmentioning
confidence: 99%